The Relationsip Between Environmental Conditions and Communitiy Behavior the Incidence of Acute Respiratory Tract Infections (ARI) in Toddlers at the Lapandew - Eky Endriana Amiruddin; Nurkasmadeli; Taswin; Rininta Andriani; Wahyuddin; Muhamad Subhan; Darsal Zulfakar David (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the relationship between environmental conditions and community behavior with ARI. The type of research used is a cross sectional study. The population in the study were all toddlers and the sample was 220 respondents. Data collection techniques using questionnaires. Results showed There is a relationship between house ventilation and the incidence of ARI in toddlers p value = 0.014. residential density and the incidence of ARI in toddlers p value = 0.023. smoking habits and the incidence of ARI in toddlers p value =0.000. Habit of using wood fuel for cooking and the incidence of ARI in toddlers p value =0.000. Conclusion that all research variables, were related to the incidence of acute respiratory infections